"Wahrheitsfähigkeit" als professionelles Können - Implikationen für die Religionslehrer/innenbildung - Schoberth, Ingrid (Zeitschrift für Pädagogik und Theologie, 2016)
Christian Faith has its specific claim for truth. This paper asks how Christian education can correspond to the conviction that the truth belongs to God alone and cannot be possessed by human beings. Learning Christian religion means to find one's own way in the light of God's truth. How can this truth shape the competence of the teacher? Is truth a certain qualification to teach Christian religion? According to the specific Christian understanding, faith is not to have the truth but to search for truth. Learning Christian religion therefore means to find ways of discussing the Gospel and its relevance in my own life. Teaching competence means to be sensible for the traces of the word of God in the discourses about life and the religious tradition.
Gesehen am 04.10.2017
Keywords: Glaube; Religionslehrer; Religionsunterricht; Kompetenzorientierter Unterricht; Wahrheit